Confirmation of the Cardiac Safety of PGF2α Receptor Antagonist OBE022 in a First‐in‐Human Study in Healthy Subjects, Using Intensive ECG Assessments. Issue 8 (28th February 2018) - Täubel, Jörg; Lorch, Ulrike; Coates, Simon; Fernandes, Sara; Foley, Paul; Ferber, Georg; Gotteland, Jean‐Pierre; Pohl, Oliver
Abstract: OBE022, a new orally active prostaglandin F2α receptor antagonist (OBE022) with myometrial selectivity is being developed to reduce uterine contractions during preterm labor. This first‐in‐human study evaluated the effect of OBE022 following multiple doses on the QT interval in 23 healthy postmenopausal women, using the effect of a meal on QTc to demonstrate assay sensitivity. We report the cardiac safety outcome performed during the multiple ascending part of this trial. OBE022 was administered after a standardized breakfast on day 1 and in the fasted state from day 3 to day 9 wth a standardized lunch 4 hours after administration. Concentration–effect modeling was used to assess the effect of prodrug OBE022 and parent OBE002 on QTc after a single dose (days 1 and 3) and multiple doses (day 9). The concentration–response analysis showed the absence of QTc prolongation at all doses tested. Two‐sided 90% confidence intervals of the geometric mean Cmax for estimated QTc effects of OBE022 and OBE002 of all dose groups were consistently below the threshold of regulatory concern. The sensitivity of this study to detect small changes in the QTc was confirmed by a significant shortening of the QTc on days 1, 3, and 9 after standardized meals. This study establishes that neither prodrug OBE022 nor parent OBE002 prolong the QTc interval. The observed food effect on the QT interval validated the assay on all assessment days. Both the change from predose, premeal and the change from premeal, postdose demonstrated the specificity of the method.